Co-oxidation of As(III) and Fe(II) by oxygen through complexation between As(III) and Fe(II)/Fe(III) species. (15th October 2018) - Ding, Wei; Xu, Jing; Chen, Tao; Liu, Chengshuai; Li, Jinjun; Wu, Feng
Abstract: Previous studies have shown that the oxidation of Fe(II) by molecular oxygen can lead to the co-oxidation of As(III) at neutral pH. However, the mechanism of As(III) oxidation in the presence of Fe(II) with respect to the interaction between As(III) and Fe(II) is still unclear. In this work, we examined the oxidation of As(III) in the presence of Fe(II) in air-saturated water, which is affected by pH, co-existing phosphate, and scavengers ( tert -butanol, superoxide dismutase, catalase and dimethylsulfoxide). Results confirm that the formation of the Fe(II)–As(III) complex (formation constant, K Fe(II)–As(III) = 10 3.86 M –1 ) plays an extremely important role in the initial stage of As(III) oxidation at pH 7.25. The oxidation of Fe(II)–As(III) promotes the production of H2 O2 and colloidal ferric hydroxide. H2 O2 reacts with the Fe(II)–As(III) complex through oxidizing Fe(II) to Fe(IV), which then causes the partial oxidation (ca. 50%) of As(III). The other part of As(III) oxidation by H2 O2 occurs, in the form of Fe(III)–As(III) complex, through direct electron transfer from As(III) to H2 O2 but not through Fe(IV). This work provides new mechanistic insight into arsenic and iron redox chemistry in the environment and furthers our understanding of Fenton reactions at neutral pH. Graphical abstract: Image 1 Highlights: Fe(II)/Fe(III)–As(III) complexation occurs during co-oxidation of Fe(II) and As(III). H2 O2 produced from Fe(II) autoxidation is responsible for As(III) oxidation. H2 O2 oxidizes As(III) only via the formation of Fe(II)/Fe(III)–As(III) complexes. Fe(IV) is the active intermediate during oxidation of Fe(II)–As(III) complex by H2 O2 . As(III) complexed with Fe(III) is oxidized by H2 O2 via direct electron transfer.